Influence Of Aluminium Doping On Random Lasing In Zno Nanorods - Ramli, Nur Fadzliana (2020)
The purpose of this study is to investigate the structural, optical and random lasing characteristics from aluminium (Al) doped ZnO nanorods fabricated on ITO coated glass substrates using chemical bath deposition (CBD) technique. Different Al doping concentration 0 (ZnO), 0.25 (AZ1), 5 (AZ2), 10 (AZ3), 30 (AZ4) and 50 (AZ5) mM were explored. The majority of nanorods show a tapered structure with at the tip and voids between nanorods were more apparent with increasing Al concentration. Different doping concentration shows different average nanorod diameter between 29.22 nm and 33.80 nm. The formation of wurtzite ZnO phase with (002) as preferential orientation was confirmed by X-ray diffraction analysis.